ChemInform Abstract: Metal Phosphides: From Chemist′s Oddities to Designed Functional Materials. Issue 30 (4th July 2013) - Carenco, Sophie; Demange, Matthieu; Boissiere, Cedric; Sanchez, Clement; Mezailles, Nicolas
Abstract Review: 53 refs.